CONSUMER PROTECTION IN DIGITAL ECONOMY ERA : LAW IN INDONESIA - Rosadi, Sinta Dewi; Tahira, Zahra (Yustisia, 2018)
Developments in information and communications technology have significantly influenced and changed lives of peoples by  providing  new opportunities for consumers and businesses.  In digital economic era, an increasing number of consumers engage in e-commerce, which provides easier and faster access to products and services However it also presents some challenges for consumers that differ from offline commercial transactions. The impersonality of e-commerce weakens the relationship between businesses and consumers, thereby increasing consumer vulnerability that could lead to  to unfair commercial practices and causing uncertainty and lack of trust by consumers. Therefore,  there is a need by the government and busineese to promte and protect consumer trust in digital markets so it will not hamper development digital economy